Semi-Online Learning as a Solution to the Digital Divide in Education in Frontier, Outermost, and Disadvantaged Regions - Amanda Putri Nahumury; Rian Antony (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This research aims to explore semi-online learning practices as a solution to the digital divide in education in the Frontier, Outermost, and Disadvantaged (3T) regions. This research method uses qualitative research conducted at SMK N A Waingapu, East Sumba and SMP B Merauke, Papua. The data collection technique was through interviews and literature studies which were then analyzed using the interactive analysis technique of Miles and Huberman. This research's results indicate that both schools apply a semi-online learning model to support learning amid limited digital access. SMK N A Waingapu chose to implement a finite face-to-face learning system for students with a weak economy, while SMP B Merauke provided problem modules for students to work on at home. The main obstacle to online learning at the two schools is the digital divide. In addition, SMK N A Waingapu East Sumba and SMP B Merauke also implemented internal policies and took steps to maintain the effectiveness of learning during the Covid-19 pandemic. These steps are the implementation of Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Coronavirus Disease (Covid-19).